The handbook of Korean linguistics - Brown, Lucien; Yeon, Jaehoon (Malden, MA : Wiley-Blackwell, 2015)
"The Handbook of Korean Linguistics presents state-of-the-art overviews of linguistic research into the Korean language"--
3 Agentivity of experiencer in psych predicate alternations4 Scalarity in locative alternation; 5 "Semantic" causative alternations; 6 Concluding remarks; Notes; References; Chapter 10 Focus, Topic, and Contrast; 1 Introduction; 2 Focus; 3 Topic; 4 Contrast; 5 Conclusion; Notes; References; Chapter 11 Case Particle Ellipsis; 1 Introduction; 2 Syntactic, semantic and pragmatic factors in the use of case particle ellipsis; 3 Markedness and case particle ellipsis; 4 Information structural account (Kwon and Zribi-Hertz 2008); 5 Probability/frequency and case particle ellipsis; 6 Conclusion; Notes.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Korean language -- Research -- Handbooks, manuals, etc; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; Korean language -- Research; FOREIGN LANGUAGE STUDY / Southeast Asian Languages; Electronic books; Handbooks and manuals